Proteomic alteration of albumen by dietary vanadium in commercial egg-type layers - Xue Bai (Poultry Science, 2020)
Vanadium (V) is an ultratrace metal with the insulin-tropic properties and is often researched as the diabetes drug. However, in animals, V has been reported to have toxic effects on the development, immunity, oxidation–reduction equilibrium, gastrointestinal function, and so forth. Especially in poultry, supplementation of more than 10 mg of V/kg in the layer diets has been shown to adversely affect the egg production and egg quality. In this study, we supplemented 0 mg of V/kg, 5 mg of V/kg, and 10 mg of V/kg in the layer diets for 35 D and examined the quantitative proteomics of albumen for finding the possible target signaling pathway and mechanism of V action and made the preliminary verification. In contrast to the control group, V resulted in a significant drop in the albumen height, and in oviduct ampulla, the activity of total antioxidant capacity and glutathione peroxidase significantly decreased (P = 0.01, P = 0.02), the content of malonic dialdehyde significantly increased (P = 0.01), and the apoptosis rate significantly increased in the 5-mg V/kg and 10-mg V/kg treatment groups (P ＜ 0.01). V affected 36 differentially accumulated proteins in albumen, with 23 proteins upregulated and 13 proteins downregulated. The expressions of innate protein albumen lysozyme (Q6LEL2), vitellogenin-2 (P02845), and the F1NWD0 protein in albumen belonged to the P53 family were significantly reduced, in contrast to the control (P < 0.05), and the expression of riboflavin-binding protein (P02752) was significantly improved (P < 0.05). The Hippo signaling pathway-fly, which is suitable for the key protein P53 as the most significantly affected network, might be important for discriminating V.